Heterozygous CX3CR1 Deficiency in Microglia Restores Neuronal β-Amyloid Clearance Pathways and Slows Progression of Alzheimer's Like-Disease in PS1-APP Mice - Hickman, Suzanne E.; Allison, Elizabeth K.; Coleman, Uwanda; Kingery-Gallagher, Nathan D.; El Khoury, Joseph (Frontiers in Immunology, 2019)
CX3CR1 is a chemokine receptor expressed on microglia that binds Fractalkine (CX3CL1) and regulates microglial recruitment to sites of neuroinflammation. Full deletion of CX3CR1 in mouse models of Alzheimer’s disease have opposing effects on amyloid-β and tau pathologies raising concerns about the benefits of targeting CX3CR1 for treatment of this disease. Since most therapies achieve only partial blockade of their targets, we investigated the effects of partial CX3CR1 deficiency on the development and progression of amyloid-β deposition in the PS1-APP Alzheimer’s mouse model. We generated PS1-APP mice heterozygous for CX3CR1 (PS1-APP-CX3CR1+/-) and analyzed these mice for Alzheimer’s-like pathology. We found that partial CX3CR1 deficiency was associated with a significant reduction in Aβ levels and in senile-like plaque load in the brain as compared with age-matched PS1-APP mice. Reduced Aβ level in the brain was associated with improved cognitive function. Levels of the neuronal-expressed Aβ-degrading enzymes insulysin and matrix metalloproteinase 9, which are reduced in the brains of regular PS1-APP mice, were significantly higher in PS1-APP-CX3CR1+/- mice. Our data indicate that lowering CX3CR1 levels or partially inhibiting its activity in the brain may be a therapeutic strategy to increase neuronal Aβ clearance, reduce Aβ levels and delay progression of Alzheimer’s-Like disease. Our findings also suggest a novel pathway where microglial CX3CR1 can regulates gene expression in neurons.